Managing Autism Spectrum Disorder in the Face of Pandemic Using Internet-Based Parent-Mediated Interventions: A Systematic Review of Randomized Controlled Trials - Iyus Yosep; Stephanie Amabella Prayogo; Kelvin Kohar; Hubert Andrew; Ai Mardhiyah; Shakira Amirah; Sidik Maulana (MDPI AG, 2022)
ASD is a neurodevelopmental disorder that is primarily treated with psychosocial intervention. However, it is costly and requires extensive resources to be effective. This inaccessibility is also further worsened by the ongoing COVID-19 pandemic, making the shift to a digital approach a sensible option. Among the available ASD therapies, parent-mediated interventions (PMIs) have a broad application and lower implementation cost. Hence, this systematic review aims to evaluate the potential that telehealth-based PMI holds and explore its feasibility throughout the COVID-19 pandemic. To build up this study, a systematic search through PubMed, Scopus, ProQuest, Wiley, and Cochrane was performed until 14 January 2021. Using the preferred Reporting Items for Systematic Review and Meta-Analysis guidelines, we ultimately included six studies in the review. Each study was evaluated utilizing the Cochrane Risk of Bias (ROB)-2 tool. Generally, parents' outcomes (knowledge, satisfaction, and compliance) were higher in intervention group (E-learning) compared to control (standard treatment or wait-list). Children also showed some improvements in social skill, communication skill, and intelligence after receiving the treatment. In addition, coaching or therapist sessions were found to be crucial as adjuvant to support parents during the intervention. In conclusion, internet-based parent-mediated interventions are promising and recommended for managing ASD patients, in the face of pandemic. However, more variety in study locations is also needed, particularly in low- and middle-income countries, to tackle the knowledge and clinical application gap. Further research should be conducted with a uniform measurement tool to achieve the same perception and reliable pooled analysis.